UKURAN PERUSAHAAN DAN PROFITABILITAS SEBAGAI DETERMINAN NILAI PERUSAHAAN MANUFAKTUR DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI - Astakoni, Made (KRISNA: Kumpulan Riset Akuntansi, 2020)
This research has several objectives namely; 1) to find out and analyze the effect of company size (size) on company value; 2) to find out and analyze the effect of company size on capital structure; 3) to know and analyze the effect of profitability on capital structure; 4) to find out and analyze the effect of profitability on company value; 5) to find out and analyze the effect of capital structure on firm value; 6) to determine and analyze the role of capital structure in mediating the relationship of company size with firm value; 7) to know and analyze the role of capital structure in mediating the relationship of profitability with firm value. The population in this study are cosmetics and household use manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2011-2018. Sampling was done purposively with predetermined criteria. The data analysis of this study uses the Partial Least Square (PLS) approach. The calculation results show that the first hypothesis; which states that there is a significant positive effect between company size on firm value is not acceptable. The second hypothesis which states the size of the company (size) has a significant positive effect on capital structure is not acceptable. The third hypothesis which states profitability (profitability) has a significant negative effect on capital structure is not acceptable The fourth hypothesis which states that there is a significant positive effect between profitability on firm value can be accepted. The fifth hypothesis which states that there is a significant positive influence between capital structure on firm value cannot be accepted. Based on calculations, the capital structure variable has not been able to be a mediating variable in intervening the influence of company size on firm value. While on the other hand the capital structure variable is able to mediate in intervening the effect of profitability on firm value.